2016
DOI: 10.1016/j.watres.2016.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in extracellular polymeric substances on hydrophobic and hydrophilic membrane surfaces in a submerged membrane bioreactor

Abstract: Membrane surface hydrophilic modification has always been considered to mitigating biofouling in membrane bioreactors (MBRs). Four hollow-fiber ultrafiltration membranes (pore sizes ∼0.1 μm) differing only in hydrophobic or hydrophilic surface characteristics were operated at a permeate flux of 10 L/m(2) h in the same lab-scale MBR fed with synthetic wastewater. In addition, identical membrane modules without permeate production (0 L/m(2) h) were operated in the same lab-scale MBR. Membrane modules were autops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 62 publications
5
20
0
4
Order By: Relevance
“…Higher PN content on the membrane surface during the steady membrane fouling stage was also reported in a previous report [8]. Matar et al investigated the temporal changes in EPS on hydrophobic and hydrophilic membrane surfaces in a lab-scale MBR; they found that the same type of organic foulants developed over time on the different membrane surface and the PN dominated the EPS components [8]. Regardless of microbe metabolism within the biofouling layer, the increment of PN at this stage was likely mainly caused by adsorption from the buck liquor by the initial fouling layer.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Higher PN content on the membrane surface during the steady membrane fouling stage was also reported in a previous report [8]. Matar et al investigated the temporal changes in EPS on hydrophobic and hydrophilic membrane surfaces in a lab-scale MBR; they found that the same type of organic foulants developed over time on the different membrane surface and the PN dominated the EPS components [8]. Regardless of microbe metabolism within the biofouling layer, the increment of PN at this stage was likely mainly caused by adsorption from the buck liquor by the initial fouling layer.…”
Section: Resultssupporting
confidence: 84%
“…A significant increase in PN was observed for S2, which constituted about 74.11% of the total EPS. Higher PN content on the membrane surface during the steady membrane fouling stage was also reported in a previous report [8]. Matar et al investigated the temporal changes in EPS on hydrophobic and hydrophilic membrane surfaces in a lab-scale MBR; they found that the same type of organic foulants developed over time on the different membrane surface and the PN dominated the EPS components [8].…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…However, contradictory results have been reported. For example, Matar et al [17] studied the effect of hydrophobic and hydrophilic membrane surfaces in MBR, and their results showed that fouling behavior in MBR processes are much less dependent on hydrophilicity than previously thought. Choi et al [18] reported that pore structure had a greater influence on the development of membrane fouling than the hydrophilicity of the membrane surface.…”
Section: Introductionmentioning
confidence: 99%